Solid-state battery and method for manufacturing same

The solid-state battery design addresses the environmental and weight issues in existing manufacturing processes by using a novel lamination and sealing method with insulating spacers and hot melt adhesives, reducing the need for ultra-low dew point environments and eliminating stainless steel support plates.

JP7657098B2Active Publication Date: 2025-04-04HONDA MOTOR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021090851
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-31
Publication Date
2025-04-04
Estimated Expiration
2041-05-31

AI Technical Summary

Technical Problem

Existing solid-state battery manufacturing processes require ultra-low dew point environments and use heavy stainless steel support plates, increasing environmental impact and weight.

Method used

A solid-state battery design where a part of the positive and negative current collectors, electrode mixture layers, and solid electrolyte layer are laminated between sealing sheets, with insulating spacers and hot melt adhesives used for sealing, reducing the need for ultra-low dew point environments and eliminating the need for stainless steel support plates.

Benefits of technology

This approach reduces environmental impact and weight by eliminating the need for ultra-low dew point environments and using lighter sealing materials, while maintaining the integrity and performance of the solid-state battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657098000002
    Figure 0007657098000002
  • Figure 0007657098000003
    Figure 0007657098000003
  • Figure 0007657098000004
    Figure 0007657098000004
Patent Text Reader

Abstract

To provide a solid-state battery which is capable of reducing an environmental load during manufacture and can be made lightweight.SOLUTION: In a solid-state battery 10, a part of a positive electrode collector 12, a positive electrode mixture layer 13, a solid electrolyte layer 14, a negative electrode mixture layer 15 and a part of a negative electrode collector 16 are successively laminated between a first encapsulation sheet 11A and a second encapsulation sheet 11B. In the solid-state battery 10, an insulation spacer 17 is present around the solid electrolyte layer 14, a first hot-melt adhesive 18A is interposed between the first encapsulation sheet 11A and the insulation spacer 17, and a second hot-melt adhesive 18B is interposed between the second encapsulation sheet 11B and the insulation spacer 17. In the solid-state battery 10, a third hot-melt adhesive is interposed between the first encapsulation sheet 11A and a positive electrode tab, and a fourth hot-melt adhesive is interposed between the second encapsulation sheet 11B and a negative electrode tab.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid-state battery and a method for manufacturing a solid-state battery. [Background technology]

[0002] Lithium ion secondary batteries have been widely used as solid-state batteries with high energy density. As an example of the lithium ion secondary battery, a solid-state lithium ion battery is known in which a positive electrode current collector, a positive electrode composite layer, a solid electrolyte layer, a negative electrode composite layer, and a negative electrode current collector are sequentially stacked.

[0003] A known method for manufacturing a solid-state lithium-ion battery is to press a positive electrode current collector, a positive electrode composite layer, a solid electrolyte layer, a negative electrode composite layer, and a negative electrode current collector in a stacked state to obtain a cell, and then seal the cell with a laminate film while sandwiching the cell between stainless steel support plates (see, for example, Patent Document 1). Another known method is to press a stainless steel support plate, a positive electrode current collector, a positive electrode composite layer, a solid electrolyte layer, a negative electrode composite layer, a negative electrode current collector, and a stainless steel support plate in a stacked state to obtain a cell, and then seal the cell with a laminate film. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-10786 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, when the cell is not sealed, the positive electrode mixture layer, the solid electrolyte layer, and the negative electrode mixture layer are not sealed, so an ultra-low dew point environment with a dew point of -70°C or less is required, which increases the environmental load. In addition, a stainless steel support plate is used when sealing with a laminate film, which increases the weight of the solid-state lithium-ion battery.

[0006] An object of the present invention is to provide a solid-state battery that can reduce the environmental impact during production and can be made lighter. [Means for solving the problem]

[0007] In one aspect of the present invention, in a solid-state battery, a part of a positive electrode current collector, a positive electrode composite layer, a solid electrolyte layer, a negative electrode composite layer, and a part of a negative electrode current collector are sequentially laminated between a first sealing sheet and a second sealing sheet, an insulating spacer is present around the solid electrolyte layer, a first hot melt adhesive is interposed between the first sealing sheet and the insulating spacer, a second hot melt adhesive is interposed between the second sealing sheet and the insulating spacer, a third hot melt adhesive is interposed between a region of the positive electrode current collector where the positive electrode composite layer is not formed and the first sealing sheet, and a fourth hot melt adhesive is interposed between a region of the negative electrode current collector where the negative electrode composite layer is not formed and the second sealing sheet.

[0008] The insulating spacer may also be present around the positive electrode mixture layer.

[0009] Another aspect of the present invention is a method for producing the above-mentioned solid-state battery, comprising a step of sequentially arranging a portion of the positive electrode current collector, the positive electrode composite layer, the solid electrolyte layer, the negative electrode composite layer, and a portion of the negative electrode current collector between the first sealing sheet and the second sealing sheet, and heat pressing the first hot melt adhesive, the insulating spacer, and the second hot melt adhesive in that order, wherein the first sealing sheet has the third hot melt adhesive formed in a portion of an area facing a region of the positive electrode current collector where the positive electrode composite layer is not formed, and the second sealing sheet has the fourth hot melt adhesive formed in a portion of an area facing a region of the negative electrode current collector where the negative electrode composite layer is not formed. Effect of the Invention

[0010] According to the present invention, it is possible to provide a solid-state battery that can reduce the environmental impact during production and can also be made lighter. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a diagram illustrating an example of a solid-state battery according to an embodiment of the present invention. [Diagram 2] 2A to 2C are diagrams illustrating a method for manufacturing the solid-state battery of FIG. [Diagram 3] 2A to 2C are diagrams illustrating a method for manufacturing the solid-state battery of Example 1. [Figure 4] 2A to 2C are diagrams illustrating a method for manufacturing the solid-state battery of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.

[0013] FIG. 1 shows an example of the solid-state battery of this embodiment.

[0014] In solid-state battery 10, a part of positive electrode current collector 12, positive electrode mixture layer 13, solid electrolyte layer 14, negative electrode mixture layer 15, and a part of negative electrode current collector 16 are sequentially laminated between first sealing sheet 11A and second sealing sheet 11B. Here, in solid-state battery 10, insulating spacer 17 is present around solid electrolyte layer 14, first hot melt adhesive 18A is interposed between first sealing sheet 11A and insulating spacer 17, and second hot melt adhesive 18B is interposed between second sealing sheet 11B and insulating spacer 17.

[0015] Here, the region of the positive electrode current collector 12 where the positive electrode mixture layer 13 is formed functions as a positive electrode, and the region of the positive electrode current collector 12 where the positive electrode mixture layer 13 is not formed functions as a positive electrode tab. In addition, the region of the negative electrode current collector 16 where the negative electrode mixture layer 15 is formed functions as a negative electrode, and the region of the negative electrode current collector 16 where the negative electrode mixture layer 15 is not formed functions as a negative electrode tab.

[0016] In addition, a third hot melt adhesive is interposed between the first sealing sheet 11A and the positive electrode tab, and a fourth hot melt adhesive is interposed between the second sealing sheet 11B and the negative electrode tab.

[0017] Incidentally, insulating spacer 17 may also be present around positive electrode mixture layer 13 .

[0018] The solid-state battery 10 may also be sealed with a laminate film.

[0019] Examples of materials constituting the laminate film include aluminum.

[0020] FIG. 2 shows an example of a method for manufacturing the solid-state battery 10.

[0021] The manufacturing method of solid-state battery 10 includes a step of sequentially arranging a part of positive electrode current collector 12, positive electrode composite layer 13, solid electrolyte layer 14, negative electrode composite layer 15, and a part of negative electrode current collector 16 between first sealing sheet 11A and second sealing sheet 11B, and sequentially arranging first hot melt adhesive 18A, insulating spacer 17, and second hot melt adhesive 18B, and then performing heat pressing. When performing heat pressing in an atmospheric environment, it is necessary to seal in advance with a PPS film or the like.

[0022] Here, the first sealing sheet 11A has a third hot melt adhesive 21A formed in a part of the area facing the positive electrode tab, and the second sealing sheet 11B has a fourth hot melt adhesive 21B formed in a part of the area facing the negative electrode tab.

[0023] In the cell obtained as described above, the positive electrode mixture layer 13, the solid electrolyte layer 14, and the negative electrode mixture layer 15 are sealed by the first sealing sheet 11A, the second sealing sheet 11B, the insulating spacer 17, the first hot melt adhesive 18A, and the second hot melt adhesive 18B. Therefore, an ultra-low dew point environment is not required in the subsequent process, and the environmental load is reduced. In addition, the weight of the solid battery 10 is reduced because the first sealing sheet 11A and the second sealing sheet 11B are used.

[0024] The pressure during the heat press is not particularly limited, but is, for example, 100 MPa or more and 2000 MPa or less.

[0025] The temperature during the heat press is not particularly limited, but is, for example, 100° C. or higher and 2000° C. or lower.

[0026] The heat press time is not particularly limited, but is, for example, from 5 seconds to 600 seconds.

[0027] When the heat press is performed, a press cushioning material may be placed on the first sealing sheet 11A and under the second sealing sheet 11B, respectively, so that damage to the solid-state battery 10 is suppressed.

[0028] Examples of materials constituting the first sealing sheet 11A and the second sealing sheet 11B include resins such as polyethylene terephthalate (PET), polyphenylene sulfide (PPS), and polybutylene terephthalate (PBT), and aluminum.

[0029] A specific example of the sealing sheet is an aluminum laminate film.

[0030] The first sealing sheet 11A and the second sealing sheet 11B may be the same or different.

[0031] Examples of insulating materials constituting the insulating spacer 17 include resins such as polyethylene terephthalate (PET), polyphenylene sulfide (PPS), and polybutylene terephthalate (PBT), and glass prepregs.

[0032] The insulating spacer 17 may have a frame shape, for example.

[0033] The first hot melt adhesive 18A and the second hot melt adhesive 18B include a thermoplastic resin.

[0034] The thermoplastic resin is not particularly limited as long as it can bond the first sealing sheet 11A (or the second sealing sheet 11B) and the insulating spacer 17, and examples thereof include polypropylene, polyethylene, and the like.

[0035] An example of a commercially available thermoplastic polypropylene product is PPa-F (manufactured by DNP).

[0036] The glass transition point of the thermoplastic resin is preferably −30° C. or higher and 100° C. or lower, and more preferably −20° C. or higher and 50° C. or lower. When the glass transition point of the thermoplastic resin is −30° C. or higher, it is less likely to flow out during heat pressing, and when it is 100° C. or lower, it is easier to adhere during heat pressing.

[0037] The first hot melt adhesive 18A and the second hot melt adhesive 18B may be the same or different.

[0038] The first hot melt adhesive 18A and the second hot melt adhesive 18B may have a frame shape, for example.

[0039] The third hot melt adhesive 21A and the fourth hot melt adhesive 21B contain a thermoplastic resin.

[0040] The thermoplastic resin is not particularly limited as long as it can bond the first sealing sheet 11A (or the second sealing sheet 11B) and the positive electrode tab (or the negative electrode tab), and examples thereof include polypropylene, polyethylene, and the like.

[0041] An example of a commercially available thermoplastic polypropylene product is PPa-F (manufactured by DNP).

[0042] The glass transition point of the thermoplastic resin is preferably −30° C. or higher and 100° C. or lower, and more preferably −20° C. or higher and 50° C. or lower. When the glass transition point of the thermoplastic resin is −30° C. or higher, it is less likely to flow out during heat pressing, and when it is 100° C. or lower, it is easier to adhere during heat pressing.

[0043] The third hot melt adhesive 21A and the fourth hot melt adhesive 21B may be the same as or different from each other. Also, the third hot melt adhesive 21A and the fourth hot melt adhesive 21B may be the same as or different from the first hot melt adhesive 18A or the second hot melt adhesive 18B.

[0044] The third hot melt adhesive 21A and the fourth hot melt adhesive 21B may have a rod-like shape, for example.

[0045] The method for manufacturing the solid-state battery 10 may further include a step of sealing the cell with a laminate film.

[0046] Examples of materials constituting the laminate film include aluminum.

[0047] Examples of the solid-state battery 10 include a semi-solid lithium ion battery, an all-solid lithium ion battery, and an all-solid fluoride ion battery.

[0048] Positive electrode current collector 12, positive electrode mixture layer 13, solid electrolyte layer 14, negative electrode mixture layer 15, and negative electrode current collector 16 can each be made of a known material.

[0049] In the following, a case where the solid-state battery 10 is an all-solid-state lithium ion battery will be described.

[0050] The positive electrode current collector 12 is not particularly limited, but examples thereof include metal foil.

[0051] The metal that constitutes the metal foil may be, for example, aluminum.

[0052] Positive electrode mixture layer 13 contains a positive electrode active material, and may further contain other components.

[0053] Examples of the other components include a solid electrolyte, a conductive assistant, and a binder.

[0054] The positive electrode active material is not particularly limited as long as it is capable of absorbing and releasing lithium ions. For example, LiCoO2, Li(Ni 5 / 10 Co 2 / 10 Mn 3 / 10 )O2、 Li(Ni) 6 / 10 Co 2 / 10 Mn 2 / 10 )O 2、 Li(Ni) 8 / 10 Co 1 / 10 Mn 1 / 10 )O 2、 Li(Ni) 0.8 Co 0.15 Al 0.05 )O 2、 Li(Ni) 1 / 6 Co 4 / 6 Mn 1 / 6 )O 2、 Li(Ni) 1 / 3 Co 1 / 3 Mn 1 / 3 )O 2、 Examples include LiCoO4, LiMn2O4, LiNiO2, LiFePO4, lithium sulfide, and sulfur.

[0055] The solid electrolyte constituting the solid electrolyte layer 14 is not particularly limited as long as it is a material capable of conducting lithium ions, and examples thereof include oxide-based electrolytes and sulfide-based electrolytes.

[0056] Negative electrode mixture layer 15 contains a negative electrode active material, and may further contain other components.

[0057] Examples of the other components include a solid electrolyte, a conductive assistant, and a binder.

[0058] The negative electrode active material is not particularly limited as long as it is capable of absorbing and releasing lithium ions, and examples thereof include metallic lithium, lithium alloys, metal oxides, metal sulfides, metal nitrides, Si, SiO, and carbon materials.

[0059] Examples of carbon materials include artificial graphite, natural graphite, hard carbon, and soft carbon.

[0060] The negative electrode current collector 16 is not particularly limited, but examples thereof include metal foil.

[0061] The metal that constitutes the metal foil may be, for example, copper. In the following, a case where the solid-state battery 10 is a solid-state lithium ion battery will be described.

[0062] Hereinafter, a case where the solid-state battery 10 is an all-solid-state fluoride ion battery will be described.

[0063] The positive electrode current collector 12 is not particularly limited, but examples thereof include metal foil.

[0064] The metal that constitutes the metal foil may be, for example, aluminum.

[0065] Positive electrode mixture layer 13 contains a positive electrode active material, and may further contain other components.

[0066] Examples of the other components include a solid electrolyte, a conductive assistant, and a binder.

[0067] The positive electrode active material is not particularly limited as long as it is capable of absorbing and releasing fluoride ions, and examples thereof include Pb, Cu, Sn, Bi, and Ag.

[0068] The solid electrolyte constituting the solid electrolyte layer 14 is not particularly limited as long as it is a material capable of conducting fluoride ions, and examples thereof include LaF3, PbSnF4, and the like.

[0069] Negative electrode mixture layer 15 contains a negative electrode active material, and may further contain other components.

[0070] Examples of the other components include a solid electrolyte, a conductive assistant, and a binder.

[0071] The negative electrode active material is not particularly limited as long as it is capable of absorbing and releasing fluoride ions, and examples thereof include CeF3, PbF2, and the like.

[0072] The negative electrode current collector 16 is not particularly limited, but examples thereof include metal foil.

[0073] The metal that constitutes the metal foil may be, for example, gold.

[0074] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and the above embodiment may be modified as appropriate within the scope of the spirit of the present invention. EXAMPLES

[0075] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0076] [Example 1] In an ultra-low dew point environment with a dew point of -70°C, a part of the positive electrode current collector 12, the positive electrode mixture layer 13, the solid electrolyte layer 14, the negative electrode mixture layer 15, and a part of the negative electrode current collector 16 were sequentially arranged between the first sealing sheet 11A and the second sealing sheet 11B, and the first hot melt adhesive 18A, the insulating spacer 17, and the second hot melt adhesive 18B were sequentially arranged, and the resultant was sealed with a PPS film. At this time, the third hot melt adhesive 21A was formed in the region of the first sealing sheet 11A facing the positive electrode tab, and the fourth hot melt adhesive 21B was formed in the region of the second sealing sheet 11B facing the negative electrode tab (see FIG. 3). In addition, a member in which a positive electrode mixture layer 13 was formed on a part of a positive electrode current collector 12, and a member in which a negative electrode mixture layer 15 and a solid electrolyte layer 14 were sequentially laminated on a part of a negative electrode current collector 16 were used.

[0077] Next, in an atmospheric environment, a press cushioning material 42 was fixed with a heat-resistant tape 41 on the top of the first sealing sheet 11A and on the bottom of the second sealing sheet 11B (see FIG. 4), and then heat-pressed under the following heat-pressing conditions to obtain a cell.

[0078] Pressure: 382MPa Temperature: 150℃ Time: 30 seconds Heat-resistant tape 41: Kapton adhesive tape (manufactured by Teraoka Manufacturing Co., Ltd.) Press cushioning material 42: 80mm x 80mm Paco Pad (made by Pacotan Technology) As a result, insulating spacer 17 was present around positive electrode mixture layer 13 and solid electrolyte layer 14. In addition, third hot melt adhesive 21A was interposed between first sealing sheet 11A and the positive electrode tab, and fourth hot melt adhesive 21B was interposed between second sealing sheet 11B and the negative electrode tab.

[0079] Next, in an atmospheric environment, the PPS film, the heat-resistant tape 41, and the press cushioning material 42 were removed from the cell, and then tab leads were welded to the positive and negative tabs. In addition, the cell was sandwiched between aluminum laminate films for batteries, and after welding on two sides, the cell was placed in a vacuum sealer and vacuum-sealed to produce an all-solid-state lithium-ion battery.

[0080] Here, the materials used in producing the solid-state lithium-ion battery are as follows.

[0081] First sealing sheet 11A: 60 mm x 60 mm x 50 μm PET film (manufactured by Toray) Second sealing sheet 11B: 60 mm x 60 mm x 50 μm PET film (manufactured by Toray) Positive electrode current collector 12: 15 μm thick aluminum foil Positive electrode composite layer 13: 50m x 50mm x 80μm composite of ternary lithium-ion battery positive electrode material, sulfide-based solid electrolyte, conductive additive, and binder Solid electrolyte layer 14: 54m x 54mm x 300μm nonwoven fabric made by Mitsubishi Paper Mills, sulfide-based solid electrolyte, and binder mixture Negative electrode composite layer 15: 54m x 54mm x 80μm composite of graphite, sulfide-based solid electrolyte, conductive additive, and binder Negative electrode current collector 16: 10 μm thick copper foil Insulating spacer 17: 50 μm thick PET frame (made by Toray) First hot melt adhesive 18A: PPa-F frame with a thickness of 50 μm (manufactured by DNP) Second hot melt adhesive 18B: 50 μm thick PPa-F frame (manufactured by DNP) Third hot melt adhesive 21A: Hanger-shaped component made of PPa-F with a thickness of 50 μm (manufactured by DNP) Fourth hot melt adhesive 21B: Hanger-shaped component made of PPa-F with a thickness of 50 μm (manufactured by DNP)

[0082] [Comparative Example 1] In an ultra-low dew point environment with a dew point of -70°C, a stainless steel support plate, positive electrode current collector 12, positive electrode mixture layer 13, solid electrolyte layer 14, negative electrode mixture layer 15, negative electrode current collector 16, and a stainless steel support plate were laminated in this order and sealed with a PPS film.

[0083] Next, the container was pressed in an atmospheric environment while still sealed with the PPS film to obtain a cell.

[0084] Next, in an ultra-low dew point environment with a dew point of -70°C, the PPS film was removed from the cell, and tab leads were welded to the positive and negative tabs. The cell was then sandwiched between aluminum laminate film for batteries, and two sides were welded together. The cell was then placed in a vacuum sealer and vacuum sealed to produce an all-solid-state lithium-ion battery.

[0085] Next, the characteristics of the all-solid-state lithium-ion battery were evaluated.

[0086] [Discharge capacity and specific capacity] The all-solid-state lithium-ion battery was assembled in a jig, confined under a confining pressure of 60 MPa, and left at the measurement temperature (25°C) for 1 hour, after which a constant current charge was performed at 8.4 mA up to 4.2 V. Next, the all-solid-state lithium-ion battery was left for 15 minutes, and then a constant current discharge was performed at a current value of 8.4 mA up to 2.6 V. Next, the above operation was repeated twice. Next, the confining pressure was lowered to 1 MPa, and the above operation was performed. The discharge capacity at the time of discharge at a confining pressure of 1 MPa was taken as the discharge capacity (mAh). In addition, the discharge capacity was divided by the mass of the positive electrode active material of the all-solid-state lithium-ion battery to obtain the specific capacity (mAh / g).

[0087] For the obtained discharge capacity, the current value at which discharge can be completed in 1 hour was defined as 1C.

[0088] [DC resistance] The all-solid-state lithium-ion battery after measuring the discharge capacity was left at the measurement temperature (25°C) for 1 hour, and then constant current charging was performed at a charge rate of 0.2C, and the charge level (SOC (State of Charge)) was adjusted to 50% and left for 10 minutes. Next, pulse discharge was performed at a discharge rate of 0.5C for 10 seconds, and the voltage when discharged for 10 seconds was measured. Then, the horizontal axis was the current value and the vertical axis was the voltage, and the voltage when discharged for 10 seconds was plotted against the discharge rate of 0.5C. Next, the all-solid-state lithium-ion battery was left for 10 minutes, and then supplementary charging was performed to return the SOC to 50%, and the all-solid-state lithium-ion battery was left for 10 minutes. Next, the above operation was performed at each discharge rate of 1.0C, 1.5C, 2.0C, 2.5C, and 3.0C, and the voltage when discharged for 10 seconds was plotted against each discharge rate. Then, the slope of the approximation line obtained by the least squares method from each plot was taken as the DC resistance (mΩ).

[0089] [Coulombic efficiency] The coulombic efficiency was calculated by dividing the discharge capacity at the time of discharge at a confining pressure of 1 MPa by the charge capacity.

[0090] Table 1 shows the evaluation results of the characteristics of the all-solid-state lithium-ion battery.

[0091] [Table 1]

[0092] From Table 1, it can be seen that the discharge capacity, specific capacity, DC resistance and Coulomb efficiency of the all-solid-state lithium ion battery of Example 1 are equivalent to those of the all-solid-state lithium ion battery of Comparative Example 1 and are within a practical range. [Explanation of symbols]

[0093] 10 solid state battery 11A First sealing sheet 11B Second sealing sheet 12 Positive electrode current collector 13 Positive electrode mixture layer 14 Solid electrolyte layer 15 Negative electrode composite layer 16 Negative electrode current collector 17 Insulating spacer 18A First Hot Melt Adhesive 18B Secondary hot melt adhesive 21A Third Hot Melt Adhesive 21B Fourth Hot Melt Adhesive

Claims

1. a part of a positive electrode current collector, a positive electrode mixture layer, a solid electrolyte layer, a negative electrode mixture layer, and a part of a negative electrode current collector are sequentially laminated between a first sealing sheet and a second sealing sheet, A frame-shaped insulating spacer is present around the solid electrolyte layer, A frame-shaped first hot melt adhesive is interposed between the first sealing sheet and the insulating spacer, A frame-shaped second hot melt adhesive is interposed between the second sealing sheet and the insulating spacer, a rod-shaped third hot melt adhesive is interposed between a region of the positive electrode current collector where the positive electrode mixture layer is not formed and the first sealing sheet, a rod-shaped fourth hot melt adhesive is interposed between a region of the negative electrode current collector where the negative electrode mixture layer is not formed and the second sealing sheet, The solid-state battery, wherein the first sealing sheet and the second sealing sheet contain a resin.

2. The solid-state battery according to claim 1 , wherein the insulating spacer is also present around the positive electrode mixture layer.

3. A method for producing the solid-state battery according to claim 1 or 2, comprising the steps of: the step of sequentially arranging a portion of the positive electrode current collector, the positive electrode mixture layer, the solid electrolyte layer, the negative electrode mixture layer, and a portion of the negative electrode current collector between the first sealing sheet and the second sealing sheet, and heat pressing the first hot melt adhesive, the insulating spacer, and the second hot melt adhesive in that order; the first sealing sheet has the third hot melt adhesive formed in a part of a region of the positive electrode current collector facing a region where the positive electrode mixture layer is not formed, the second sealing sheet has the fourth hot melt adhesive formed in a part of an area of ​​the negative electrode current collector that faces an area where the negative electrode mixture layer is not formed.

Citation Information

Patent Citations

  • electrochemical element

    JP1993031220U

  • All solid secondary battery and manufacturing method therefor

    JP2017010786A